The Role of Nuclear Forensics for Determining the Origin of Nuclear Materials Out of Regulatory Control and Nuclear Security - Lekhnath Ghimire; Edward Waller (International Journal of Nuclear Security, 2022)
The international community recognizes the rise in theft and illicit trafficking of nuclear materials and radioactive sources—for malicious use and nuclear terrorism—as a serious threat. That is why a well-developed nuclear forensics capability is an integral part of a robust nuclear security program and a key element of nuclear security infrastructure. Both pre- and post-detonation nuclear forensics are vital for controlling theft and illicit trafficking of nuclear materials, as well as identifying and tracing their sources. Nuclear forensics analysis and interpretation processes for nuclear security is a systematic process that includes: (1) sample collection and categorization techniques and (2) detailed nuclear forensics analytical plans, which are a laboratory analysis of physical and chemical properties of the collected or seized nuclear and radioactive materials. Besides nuclear materials, the non-nuclear and biological materials present in seized nuclear materials can also provide important information about the source and origin of nuclear materials. Upon complete analysis of the seized materials, the data interpretation to trace the origin of the nuclear and radiological materials is one of the most critical steps to identifying the origin of the materials, which depends on the availability of similar data to compare. So, each country should have its own incident register system (IRS) and collaborate with the International Technical Working Group (ITWG), Incident and Trafficking Database (ITDB), and IAEA for data sharing and interpretation.
Keywords: Illicit trafficking; nuclear security; nuclear forensics; pre and post detonation forensics; characterization; interpretation; source tracing